A Systematic Literature Review on the Influence of Religious Education on Character Development and Academic Achievement in Middle School Students - Nisrina Huwaida Qurrottu Aini; Mutohharun Jinan; Hakimuddin Salim; Fadhilla Nangroe Anggraini; Farouq Muhammad Najib (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Religious education plays an important role in the character formation and academic achievement of high school students. In the context of an increasingly complex and plural world, religious education serves not only as a means to introduce certain religious teachings, but also as a tool to shape the character of students through important moral values such as discipline, tolerance, and responsibility. This study aims to review the influence of religious education on the character development and academic achievement of high school students, focusing on various models and approaches that can improve both. The method used is a systematic literature review (SLR), referring to the PRISMA 2020 guidelines, to analyze various relevant empirical studies from various scientific sources. The results of the study show that religious education that integrates the values of moderation and multiculturalism has a positive impact on the formation of students' character, as well as improving their academic achievement. The use of digital technology, such as Immersive Virtual Reality (IVR), has also been proven to enrich religious learning experiences, increase emotional engagement, and deepen students' understanding of religious teachings. However, there are challenges in optimizing the involvement of parents and communities in a more holistic religious education process. Therefore, further research is needed to develop a more effective religious education model in supporting the development of students' character and academic achievement. This research emphasizes the importance of integration between religious education, moral values, and technology to create a better learning environment and support students' academic success.